2015
DOI: 10.1016/j.microrel.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of C-Line plot technique for the characterization of edge effects in acoustic imaging: A case study using flip chip package geometry

Abstract: Edge effect is a common phenomenon observed in Acoustic micro imaging of microelectronic packages. In this paper, using flip chip package geometry as a test vehicle, finite element modelling is carried out to study the fundamental mechanism of the edge effect phenomenon. C-line plot technique is developed for characterisation of edge effects in acoustic C-scan images, in particular solder joint C-scan images. Simulated results are compared to experimental results. Results reveal that edge effect generation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Finite element modelling for acoustic micro imaging of microelectronic packages was carried out in our previous research to investigate the acoustic wave propagation inside a package and the generation mechanism of edge effect [8,9] of the FEM modeling undertaken to describe the contrast in the UT-imaging of solder bumps using an SAM can be found in [8].…”
Section: Finite Element Modelling For Acoustic Micro Imaging Of Micromentioning
confidence: 99%
See 2 more Smart Citations
“…Finite element modelling for acoustic micro imaging of microelectronic packages was carried out in our previous research to investigate the acoustic wave propagation inside a package and the generation mechanism of edge effect [8,9] of the FEM modeling undertaken to describe the contrast in the UT-imaging of solder bumps using an SAM can be found in [8].…”
Section: Finite Element Modelling For Acoustic Micro Imaging Of Micromentioning
confidence: 99%
“…Figure 6, it can be seen that the Dip-Y reaches a quasi-saturation point beyond a crack of 55µm. This is due to the edge effect mainly occurring in regions at and close to the edge of the UBM structures [8]. Due to the transducer resolution limitation, current scanning acoustic microscopy cannot quantitatively evaluate small defects directly through C-scan images.…”
Section: Finite Element Modelling For Acoustic Micro Imaging Of Micromentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters in Equation (2) Figure 9a shows the obtained B-scan image using Model A. In order to study edge effect, a C-Line plot [4,5] as shown in Figure 9b is generated by gating the B-scan image to the desired interface, similar to real C-scan imaging. Since we are interested in the silicon die-tosolder bump interface, the gate is set to select that interface.…”
Section: Virtual Transducer and Characterizationmentioning
confidence: 99%
“…In our earlier study, finite element modelling was proposed to investigate acoustic propagation inside microelectronic packages, and the basic finite element model and preliminary results were reported in [4]. In [5,6], C-line plot technique was developed for characterisation of edge effects in acoustic C-scan images, in particular solder joint C-scan images. In this paper, the model is further improved by introducing the dynamic meshing, more suitable material properties, characterisation of virtual transducer, etc.…”
Section: Introductionmentioning
confidence: 99%